2009
DOI: 10.1002/jms.1628
|View full text |Cite
|
Sign up to set email alerts
|

Effect of urea surface modification and photocatalytic cleaning on surface‐assisted laser desorption ionization mass spectrometry with amorphous TiO2 nanoparticles

Abstract: We have investigated the effect of urea surface modification and the photocatalytic cleaning on surface-assisted laser desorption ionization mass spectrometry (SALDI-MS) with amorphous TiO2 nanoparticles for the reduction of the background noise and the improvement of the sensitivity. In the use of nanoparticles of high surface area, chemical background signals arising from ambient environments and organic contaminants can frequently be serious problems below 500 Da, possibly reducing the advantages of the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
(24 reference statements)
0
18
0
Order By: Relevance
“…6). Under the UV-laser irradiation on titania based SALDI-MS, it was reported that electrons are excited from the valence band to the conduction band of titania, producing oxidative holes to drive in-source oxidation reactions and reductive electrons to induce in-source reactions of analytes in SALDI-MS. 33), 48), 49) In this study, such UV-laser induced photocatalytic oxidation reactions were observed in the case of amorphous (or titania)-type titania with strong photocatalytic e#ects, but not for rutile-type titania with weak photocatalytic e#ects. As shown in Fig.…”
Section: Laser Threshold For Titania-based Saldi-msmentioning
confidence: 56%
See 1 more Smart Citation
“…6). Under the UV-laser irradiation on titania based SALDI-MS, it was reported that electrons are excited from the valence band to the conduction band of titania, producing oxidative holes to drive in-source oxidation reactions and reductive electrons to induce in-source reactions of analytes in SALDI-MS. 33), 48), 49) In this study, such UV-laser induced photocatalytic oxidation reactions were observed in the case of amorphous (or titania)-type titania with strong photocatalytic e#ects, but not for rutile-type titania with weak photocatalytic e#ects. As shown in Fig.…”
Section: Laser Threshold For Titania-based Saldi-msmentioning
confidence: 56%
“…Among the various types of materials proposed for SALDI-MS, titania (TiO 2 ) appears to be a promising candidate, because its physicochemical properties permit SALDI performance to be improved: (1) a high UV absorbance with a large bandgap (bulk anatase: 3.2 eV), (2) good chemical stability under a variety of pH conditions and under ambient air, (3) surface modification with various functional groups, 33) and (4) possible morphology control of titania such as porous structures with a high surface area. 18), 19) In addition, in contrast to DIOS-MS that is used for analyzing analytes with a molecular weight of ῑ6 kDa, 34) titaniabased SALDI-MS can be used to analyze high molecular weight proteins (ῑ24 kDa) as well as small molecules and has the advantage that phosphopeptides are specifically adsorbed.…”
Section: )῍9)mentioning
confidence: 99%
“…Nowadays, organosilane precursors bearing functional groups such as amino [12][13][14][15][16][17][18][19][20][21][22], thiol, carboxyl, phosphate, vinyl [23][24][25], cyanide [26], phenyl [24,27] or sulphhydryl groups are readily available. Despite the wide variety of silane precursors available for surface modification, the majority of studies have employed aminosilanes, in particular 3-aminopropyltriethoxysilane (APTES) [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The core metal and functional groups of the NPs can be modified to ionize analytes on the basis of specific chemical properties. The core metals gold [11], silver [12][13][14], titanium dioxide [15], and their mixture [16] have been used in SALDI-MS analysis. SALDI-MS analyses using their NPs have detected analytes that are different from those used in general matrices or to enhance the signal intensities from the molecules.…”
mentioning
confidence: 99%